1974
DOI: 10.1111/j.1532-5415.1974.tb04816.x
|View full text |Cite
|
Sign up to set email alerts
|

Presenile Dementia: Further Experience with an Anticoagulant‐Psychotherapy Regimen*

Abstract: The principles of an anticoagulant-psychotherapy regimen for presenile dementia are discussed. Short histories are given of 10 patients (including one with Huntington's chorea as well as dementia) who responded well to this treatment. It is important to keep the blood prothrombin time at 2.0-2.5 times the control time. The earlier treatment is started, the better the result. Even in cases in which there is n o significant improvement, the prevention of further deterioration is of great value. If properly contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1976
1976
1981
1981

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Also discussed was the proposition that these diseases, as well as organic dementia due to arteriosclerosis and several other similar syndromes, have the same cause, i.e., cerebrovascular insufficiency. Brain ischemia as a fundamental factor in dementia has been even more firmly established by our continuing success with treatment (3). Additional support is provided by the numerous reports in the literature that indicate the various ways in which the brain can be deprived of blood.…”
mentioning
confidence: 99%
“…Also discussed was the proposition that these diseases, as well as organic dementia due to arteriosclerosis and several other similar syndromes, have the same cause, i.e., cerebrovascular insufficiency. Brain ischemia as a fundamental factor in dementia has been even more firmly established by our continuing success with treatment (3). Additional support is provided by the numerous reports in the literature that indicate the various ways in which the brain can be deprived of blood.…”
mentioning
confidence: 99%
“…Because of this hopeless prognosis and because she showed early signs of organic dementia (in‐distinguishable from presenile dementia except that she had choreic movements), she was offered a trial of treatment that the senior author had found effective in many patients with presenile dementia (2). The entire situation was explained to her and her husband and they requested the recommended trial.…”
Section: Case Reportmentioning
confidence: 99%
“…Treatment was begun in December 1973 after they had signed an “informed consent” form. Anticoagulant therapy was combined with psychotherapy which includes the cooperation of the patient and the family, as described in previous papers (24). Warfarin sodium (Coumadin) was used as the anticoagulant.…”
Section: Case Reportmentioning
confidence: 99%
“…Sometimes the hypochondriacal symptom is the presenting problem. For example, in a previous paper (4) we described the case of a 60‐year‐old man who complained of pain in the chest wall since the time of a surgical incision there. He had such persistent pain that a sympathectomy was performed to provide some relief.…”
Section: Hypochondriasismentioning
confidence: 99%